(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper explores the personality characteristics of the five Pandava brothers—Yudhishthira, Bhima, Arjuna, Nakula, and Sahadeva—from the Mahabharata through the lens of Alfred Adler’s Birth Order Theory. The study situates this psychological analysis within the framework of Indigenous Knowledge Systems (IKS), emphasizing how ancient Indian epics convey implicit psychological insights. Through qualitative content analysis, the research identifies patterns aligning with Adler’s conceptualization of first-born, middle-born, and youngest child traits. The findings reveal a synthesis between cultural narratives and universal psychological principles, demonstrating the continuing relevance of indigenous literature to modern psychology.